GIS Mineral Potential Mapping for Bauxite Deposits Using Analytical Hierarchy Process (AHP) Method in West Kalimantan, Indonesia - , YANG VIRINRATH, Dr. Lucas Donny Setijadji ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main purpose of this research aims to study spatial association between known bauxite deposits occurrences and certain geological features that control their occurrence and to delineate prospective areasfor bauxite deposits to be discovered in the future. The study area is located in West Kalimantan, Indonesia,which is now the most important bauxite district in the country. The study area is part of tropical region and is bound by latitudes 1 o 0âS to 1 o 0âN and longitudes 109 o to111 o E.The western part of study area is characterized by a wide, mostly swampy alluvial or littoral plain interrupted in a few places and the eastern part is occupied by hilly and locally low mountainous country which forms the foothills of the Schwaner Mountains. Bauxite prospectivity mapping is conducted by the mineral potential mapping(MPM) method using geographic information system (GIS) which is a complex analytical process that requires consideration and integration of several spatial evidences. The input data for analysis include lithological evidence, slope evidence and rock age evidence. A knowledge -driven method, i.e. analytical hierarchy process (AHP) approach is employed to assign the weight of each factor and to quantify the spatial associationof dataset. All the factors of evidence mapsare integrated using GIS to generate a mineral potential map using weights calculated from the AHP method. The result on potential map identifies several bauxite potential zones, which are classified according to the degree of probability, and have been verified based on ground check data on known deposit and mining areas.The degree of prospective areas range from 1.002 (lowest) to 10.02 (highest). The highestprobability area occurs in the southeastern part of the study area, associated with large bauxite deposits produced by lateritization of Cretaceous igneous rocks within undulating hills morphology thatcan be treated as the most potential site for further exploration. Between the low and high probability zones, there is moderate probability zone that is not so easily used to predict the presence of relatively smaller bauxite deposits.